Communication in Religion and Its Integrative Implications for Society - Peter. O. O. Ottuh; Mary O. Jemegbe (PINISI Discretion Review, 2021)
Looking at religion from the lens of social theory system, one cannot but, postulate that religion is an expression of the relationship that exists between human beings and the divine. This religious expression by individuals accumulates into plethora of communication within a given society. This paper is solely concerned with communication in religion and religious communication and how they play integrative role in the social cohesion of human society. Methods adopted to achieve the above task are the phenomenological and evaluative methods with support of secondary sources. The research reveals that communication in religion and religious communication are strong and essential agents of social change in any human society; and that, they have also enhanced the lives of individuals in terms of social, moral, mental, spiritual, economic and cultural well-being. The paper concludes that the communicative power of religion should not be underrated by individuals, society and government. And that religion should be used to communicate effectively and positively for the integration and development of modern society.